South Africa - the place of youth in a democracy of many faces (Alternate Horizons, 2022)
“We cannot always build the future for our youth, but we can build our youth for the future.” These wise words were expressed by President Franklin D. Roosevelt (Roosevelt 1941 cited in Palmadessa 2017). More than half of the youth of South Africa are looking for formal employment. It is therefore important to invest more in the youth. However, South Africa remains a country of many faces. It is a country of paradoxes, incongruities and ironies; where poverty and wealth are in competition, while modernity and traditionalism walk side by side. It is recognised as 'the most unequal country in the world' in terms of the enduring legacy of apartheid (Feldman & Wallace 2021). This article, therefore, seeks to understand the place of youth in South Africa’s democratic dispensation. [1] (Roosevelt, 2020).
Keywords: Youth, democracy, democratic dispensation, formal employment, unequal country, protest actions